Complete Genome Sequences of Six Copper-Resistant Xanthomonas Strains Causing Bacterial Spot of Solaneous Plants, Belonging to X. gardneri, X. euvesicatoria, and X. vesicatoria, Using Long-Read Technology - Richard, Damien; Boyer, Claudine; Lefeuvre, Pierre; Canteros, Blanca Isabel; Beni-Madhu, Shyam; Portier, Perrine; Pruvost, Olivier (2017)
Xanthomonas vesicatoria, Xanthomonas euvesicatoria, and Xanthomonas gardneri cause bacterial spot disease. Copper has been applied since the 1920s as part of integrated management programs. The first copper-resistant strains were reported some decades later. Here, we fully sequenced six Xanthomonas strains pathogenic to tomato and/or pepper and having a copper-resistant phenotype.